2017
DOI: 10.1177/1010428317705515
|View full text |Cite
|
Sign up to set email alerts
|

Noxin promotes proliferation of breast cancer cells via P38-ATF2 signaling pathway

Abstract: Noxin (also called chromosome 11 open reading frame 82 or DNA damage-induced apoptosis suppressor) is associated with anti-apoptosis and cell proliferation in response to stress signals. However, to our knowledge, the role of Noxin in regulating cell proliferation is still controversial and there are no reports of the function and clinicopathological association in breast cancer. In this study, immunohistochemistry results showed that Noxin expression was significantly correlated with advanced tumor-node-metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Our studies suggested that TIMM50 also promoted tumor proliferation and invasion in NSCLC cells via upregulating Cyclin D1 and Snail and downregulating E‐cadherin. During tumor progression, multiple signaling pathways, such as ERK, AKT, P38, and FAK, were involved in modulating the expression of Cyclin D1, Snail, and E‐cadherin . Using Western blotting analysis, we found that overexpression of TIMM50 was capable of upregulating the levels of phosphorylated ERK and P90RSK.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our studies suggested that TIMM50 also promoted tumor proliferation and invasion in NSCLC cells via upregulating Cyclin D1 and Snail and downregulating E‐cadherin. During tumor progression, multiple signaling pathways, such as ERK, AKT, P38, and FAK, were involved in modulating the expression of Cyclin D1, Snail, and E‐cadherin . Using Western blotting analysis, we found that overexpression of TIMM50 was capable of upregulating the levels of phosphorylated ERK and P90RSK.…”
Section: Discussionmentioning
confidence: 94%
“…During tumor progression, multiple signaling pathways, such as ERK, AKT, P38, and FAK, were involved in modulating the expression of Cyclin D1, Snail, and E-cadherin. [14][15][16][17][18][19][20][21] Using Western blotting analysis, we found that overexpression of TIMM50 was capable of upregulating the levels of phosphorylated ERK and P90RSK. To further test the effect induced by overexpressing TIMM50 was mediated by activating ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 97%
“… 20 These data were consistent with previously published reports that the P38-ATF2 signaling pathway promotes proliferation via transcriptional activation of key cell-cycle regulators. 21 23 A previous report showed that FAM98A, as a novel substrate of PRMT1, is arginine-methylated by PRMT1. 6 PRMT1 is associated with p38α in cells, as shown by co-immunoprecipitation, and directly methylates p38α in in vitro methylation assays.…”
Section: Discussionmentioning
confidence: 99%
“…For mRNA RT-qPCR, cDNA was reverse-transcribed from mRNA by M-MLV Reverse Transcriptase (Takara) using random primers and oligo (dT) primers. The quantification of level of target gene expression (2 -ΔΔCt ) was normalized to the endogenous GAPDH mRNA (7,22). The reaction conditions of PCR were according to the SYBR-Green qPCR Mix instruction (Bio-Rad Laboratories, Inc., Hercules, CA, USA).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%